Flow‐mediated movement of freshwater catfish, Tandanus bostocki, in a regulated semi‐urban river, to inform environmental water releases. Issue 3 (12th February 2019) - Beesley, Leah; Close, Paul G.; Gwinn, Daniel C.; Long, Matthew; Moroz, Michael; Koster, Wayne M.; Storer, Timothy
Abstract: Movement and migration of fish are critical for sustaining riverine fish populations. Water resource development alters natural flow regimes and can disconnect habitats and interfere with hydrological cues for fish movement. Environmental flow releases can counter these impacts, but to be effective they must be based on quantitative flow–biota relationships. We used radio‐telemetry to investigate the association between flow and movement of Tandanus bostocki, a plotosid fish endemic to south‐western Australia. Movement was assessed for 15 adult fish at three temporal scales: weekly, daily and bihourly to reveal seasonal patterns in movement, movement around individual flow pulses, and to describe changes in home range respectively. We used a predictive modelling approach to assess the importance of discharge and other covariates on the directional distance travelled or linear home range size. Our seasonal and flow pulse study revealed that T. bostocki undertook larger downstream movements during higher flows and smaller upstream movements during lower flows. Daily movements tended to be downstream on the ascending limb of flow pulses and upstream on the descending limb. Flow‐dependent movements at weekly or daily time scales were relatively modest (typically hundreds of metres) and were moderated by time of year and gender; however, fish underwent a synchronised 1‐km movement upstream during the known reproductive period in October. The home range study revealed that T. bostocki had larger home ranges (night‐time foraging) when baseflow was elevated. These results can assist the design of customised environmental flows in the study river and other flow‐regulated rivers.